A Molecular Analysis of Microalgae from Around the Globe to Revise Raphidonema (Trebouxiophyceae, Chlorophyta). Issue 5 (25th June 2021) - Yakimovich, Kurt M.; Gauthier, Nick P.G.; Engstrom, Casey B.; Leya, Thomas; Quarmby, Lynne M.
Abstract : We isolated five microalgal strains from alpine snow near Vancouver, Canada, which display morphological features suggestive of the genera Koliella and Raphidonema . Due to variations in cell size and shape, we could not make a clear delimitation based on morphology. We proceeded to a molecular analysis and included 22 strains from the CCCryo culture collection, previously identified as members of four closely related genera: Raphidonema, Koliella, Stichococcus, and Pseudochlorella . For greater taxonomic context in our phylogenetic analysis, we also obtained authentic strains for the type species of Koliella and Pseudochlorella, but were unable to find one for Raphidonema . To examine generic boundaries, we did a phylogenetic analysis on the rbc L gene for all strains, establishing distinct lineages. Our novel isolates fell within Raphidonema, and so we analyzed the ITS2 gene of all Raphidonema strains to delimit species. To support species delimitations, we did a Compensatory Base Change analysis using the secondary structure of the ITS2 gene to assist in aligning the sequence. We also computed a maximum likelihood phylogenetic tree to examine species clades of Raphidonema . We assigned epitypes for two Raphidonema species based on the best morphological match to strains in the ITS2 clades. We then amended their diagnoses so they can be more reliably identified using DNA sequence data. We also propose two new species, R. catena and R. monicae, that formed their own species clades according to our ITS2 analysis.